Annual Review of Development Effectiveness 2006 : Getting Results - Huppi, Monika (Independent Evaluation Group Studies, 2006)
The "results agenda" adopted by the World Bank and other donors aims to ensure that development assistance yields sustainable poverty reduction. Effective poverty reduction results from three main factors: sustained and inclusive growth, effective service delivery to the poor, and capable public sector institutions that are accountable to stakeholders for the results they achieve. The Annual Review of Development Effectiveness 2006 assembles evaluative evidence around three questions central to poverty reduction: How effectively has economic growth translated into poverty reduction in Bank-assisted countries and what factors have affected these results? What factors have led to high-quality results in areas that deliver services to the poor? What measures help raise the accountability of public institutions responsible for delivering and sustaining these results? The report identifies three key areas where the World Bank can further strengthen its effectiveness in helping countries reduce poverty. Economic growth has improved in many Bank client countries but a stronger focus on the nature of growth is needed to ensure that such growth leads to jobs for the poor and productivity increases in poorer regions and sectors where the poor earn their incomes. Consistent use of a clearly articulated results chain helps ensure that Bank country assistance programs and individual projects set realistic objectives, that key cross-sectoral constraints to achieving them are adequately considered and that due attention is given to building capacity. A realistic assessment of the political economy of governance-related reforms is needed to tailor efforts to increase the accountability of public sector institutions to local conditions